The Relationships between Physical Activity, Sleep Duration, Alcohol Consumption, and Hypertension in Adults: Meta-Analysis - Niken Putri Eka Saraspuri; Nisa Nur Kusuma (Masters Program in Public Health, 2022)
Background: Hypertension is a disease that causes damage to body systems. Risk factors for hypertension are changes in socioeconomic, environmental, and unhealthy lifestyle such as smoking, lack of physical activity, high-fat and high-calorie foods, and alcohol consumption. This study aims to analyze the relationship between physical activity, sleep duration, and alcohol consumption on the incidence of hypertension in adults with a meta-analysis study. Subjects and Method: This study is a systematic review and meta-analysis with the population: adults (>18 years old). Intervention: low physical activity, short sleep duration and frequent alcohol consumption. Comparison: moderate physical activity, normal sleep duration, and no alcohol consumption. Outcome: the incidence of hypertension. The articles used were obtained from several databases: PubMed, SpringerLink, ScienceDirect, and Google Scholar. The keywords are: “physical activity” OR exercise” AND “sleep duration” AND “alcohol consumption” AND